2015
DOI: 10.1016/j.jtcvs.2015.08.043
|View full text |Cite
|
Sign up to set email alerts
|

European multicenter experience with valve-sparing reoperations after the Ross procedure

Abstract: Valve-sparing autograft reoperations after the Ross procedure carry a low operative risk, with acceptable reintervention rates in the first postoperative decade. Patients with isolated and/or severe autograft regurgitation have an increased hazard of reintervention after valve-sparing reoperation; for these patients, careful preoperative weighing of surgical options is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…1) In the largest series to date, approximately 20% of patients required concomitant surgery to correct RVOT stenosis. 2) Here, we demonstrate that all valves can be surgically repaired or replaced safely during autograft Valve-Sparing Root Replacement Post-Ross VSRR. As more patients are considered for VSRR, coexistent mitral, tricuspid, and pulmonic valve dysfunction should not preclude salvage of the autograft valve, nor should autograft leaflet prolapse.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…1) In the largest series to date, approximately 20% of patients required concomitant surgery to correct RVOT stenosis. 2) Here, we demonstrate that all valves can be surgically repaired or replaced safely during autograft Valve-Sparing Root Replacement Post-Ross VSRR. As more patients are considered for VSRR, coexistent mitral, tricuspid, and pulmonic valve dysfunction should not preclude salvage of the autograft valve, nor should autograft leaflet prolapse.…”
Section: Discussionmentioning
confidence: 66%
“…The variant of the VSRR likely impacts durability. 2) We favor the reimplantation technique in all scenarios, regardless of complexity. 5) We have also had early success with direct autograft leaflet repair to enhance repairability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated rate of freedom from adverse outcomes of the pulmonary autograft in our study was 88% and 70% at 5 and 10 years, respectively. Regarding the reoperation method for the pulmonary autograft, previous reports have suggested a valve-sparing operation [ 17 ] under the belief that dilatation of the neo-aortic root was the main cause of aortic insufficiency. However, David et al [ 16 ] found abnormal cusps at reoperation that precluded aortic valve sparing in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reintervention remains the main concern as there is a perception that the rates are high and this may be associated with increased morbidity and mortality ( 14 , 15 ). Reports on outcomes of reintervention after Ross however persistently demonstrated that it can be performed safely and that the autograft itself can sometimes be salvaged by repair or even valve-sparing reimplantation ( 31 33 ).…”
Section: Surgical Optionsmentioning
confidence: 99%